Percepções masculinas sobre a liderança feminina na Universidade Federal do Amazonas - Batista, Ana Paula Costa Pinheiro (Brasil, 2024)
This study aims to analyze the similarities and differences in men's views on female leadership, identify the presence of stereotypical perceptions of female leadership among men, and analyze the influence of the cultural context on men's views on female leadership. The number of women in command positions has increased over the years, but the difficulties they face still remain current. Given that they are female and therefore 'weak', they could not be in superior positions to men (Silva, 2006). For this study, semi-structured interviews were carried out with twelve men linked to the Federal University of Amazonas (UFAM), all with experience under the immediate leadership of a woman. The identified perceptions were divided into two categories. The first, "Perceptions of Female Leadership", sought to analyze the similarities and differences in men's views on female leadership, as well as identify the presence of stereotypical perceptions. The second category, “Leadership Influencing Factors,” explored the influence of cultural context. The results show that men and women are equally accepted as leaders at UFAM. However, there is no active policy at the university that specifically promotes female leadership. When a woman reaches a leadership position, this process occurs naturally, without the influence of politics. The results of this study can contribute to a comprehensive analysis of men's perceptions of women's leadership. Furthermore, future quantitative studies may provide additional metrics to assess the importance of gender equality policies.